Aging and immigration policy in a representative democracy - Lena Calahorrano (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
This paper analyzes how population aging affects immigration policy in rich industrialized countries. It sets up a two-period model of a representative democracy with two overlapping generations. The government's preferred immigration rate increases with the share of retirees in the population. The paper differentiates between an economy without a pension system and one with pay-as-you-go pensions. As immigrants have more children than natives, the chosen immigration rate is contingent on the design of the pension system. If pension contributions and benefits are set freely by the government, equilibrium immigration is lower than it is in the absence of a pension system. On the contrary, it is higher if the pension level is fixed ex ante to a relatively generous level, since native workers then benefit from sharing the burden of pension contributions with the immigrants.
Keywords: J1; D78; F22; 330; demographic change; political economy; immigration policy; Migrationspolitik; Demokratie; Alternde Bevölkerung; Public Choice; Theorie